Cardioprotection of tilianin ameliorates myocardial ischemia-reperfusion injury: Role of the apoptotic signaling pathway. - Cheng Zeng; Wen Jiang; Ruifang Zheng; Chenghui He; Jianguang Li; Jianguo Xing (PLoS ONE, 2018)
Our previous research demonstrated that tilianin protects the myocardium in a myocardial ischemia reperfusion injury (MIRI) rat model and has prominent pharmacological potential as a cardiovascular drug. Our study aimed to investigate the molecular signaling implicated in the improvement of myocardial survival induced by tilianin, a flavonoid antioxidant. Tilianin (2.5, 5, and 10 mg/kg/d) or saline was orally administered to rats for 14 days. On the 15th day, ischemia was induced by ligating the left anterior descending artery for 45 min, followed by 4 h of reperfusion. The levels of MIRI-induced serum myocardial enzymes and cardiomyocyte apoptosis as well as infarct size were examined to assess the cardioprotective effects. Cardiac tissues were collected for western blot analyses to determine the protein expression of anti-apoptotic signaling molecules. In MIRI-treated rats, our results revealed that pre-administration of high dose-tilianin the reduced release of LDH, MDA, and CK-MB and increased the plasma SOD level, and significantly attenuated the infarct size. Western blot analysis showed that a remarkable rise in expression of Bcl-2 and XIAP, and decline in expression of Bax, Smac/Diablo, HtrA2/Omi, cleaved caspase-3, caspase-7 and caspase-9 was observed in the myocardium. The apoptosis index of cardiomyocytes further supports the cardioprotective effect of tilianin. Additionally, compared with the MIRI model group, pretreatment with high dose-tilianin group upregulated phosphorylated Akt and PI3K. In contrast, using the PI3K inhibitor LY294002 to block Akt activation effectively inhibited the protective effects of tilianin against MIRI. Tilianin pretreatment was beneficial for activating the PI3K/Akt signaling pathway and inhibiting myocardial apoptosis.